The Impact of Training on Employee Engagement: A Case Study at Kampala Capital City Authority - Isaac Junior Ogwang (Uganda Christian University, 2024)
Employee engagement has emerged as an essential factor for organizational success and workforce retention. In earlier times, companies concentrated mainly on providing financial incentives to drive employee motivation. However, in more recent years, the focus has shifted toward fostering employee engagement, recognizing its impact on commitment to the organization and overall productivity (Kahn, 1990). Employee engagement is typically defined as the level of emotional, mental, and physical involvement that employees have with their work and workplace (Schaufeli & Bakker, 2004). The concept of employee engagement is generally understood to encompass three main dimensions: emotional, cognitive, and physical involvement (Schaufeli & Bakker, 2004). Emotional engagement relates to how employees feel about their work, cognitive engagement pertains to how mentally connected they are with their tasks, and physical engagement refers to the effort they put into their job. Understanding these dimensions provides insight into how employees interact with their work environment and, subsequently, their levels of engagement (Rich et al., 2010).